Effects of refined, bleached and deodorized palm oil/palm stearin-based shortenings on the quality and staling of white bread - Artan, Mohamud Yasin (2011)
The objective of this research was to determine the effects of different types of refined, bleached and deodorized (RBD) palm oil/palm stearin-based shortenings on the quality and staling of white bread. For this purpose, shortenings of seven blends of RBD palm oil (PO) and palm stearin (PS) were prepared in three replications. Shortenings were blended in 100:00, 80:20, 60:40, 50:50, 40:60, 20:80 and 00:100 of PO: PS ratios, respectively. The fatty acid compositions (FA), triacylglycerols (TAG), thermal and rheological characteristics of both experimental and commercial shortenings were studied. In addition, iodine value (IV) analysis was carried out. The experiment was designed as a complete randomized design (CRD), with three separate replications. In total, seven formulations of bread were prepared, and bread made from commercial shortening was used as a control, while those made without shortening were used as comparisons with other bread samples. Bread made using emulsifiers was also used in this research. The bread samples were tested for loaf volume, specific volume, crust colour, crumb colour and texture profile analysis. Breads were investigated at ambient temperature and various aging times using differential scanning calorimetry (DSC) and texture analyzer (TA-XT2) to determine starch retrogradation and crumb firmness, respectively. The results revealed that the prominent fatty acids in the products were palmitic (46.24-63.48%), oleic (24.59-40.33%) and linoleic (6.46-9.91%). At the same time, triacylglycerols (TAG), such as OOO, OOP and OOS, were found to decrease, while PPO increased due to the increase in the palm stearin content of the shortenings. Increasing the content of palm oil in the shortenings caused a decrease in viscosity, storage modulus (G') and loss modulus (G") values. On the other hand, certain parameters such as the onset, peak and endset temperatures (ºC) were detected for both the melting and cooling data. However, increasing the palm stearin content in the samples showed increases in the onset, peak, endset temperatures and peak height, and vice versa. Likewise, increasing palm stearin content in the shortening Formulations could decrease loaf volume and specific volume. The statistical analysis showed that breads made using the shortening formulation consisted of 100% palm stearin had the highest volume and specific volume, but they were the least in terms of density. However, loaf volume, specific volume and crumb texture of the bread samples showed significant differences (p<0.05) as compared with the bread that was made without shortening. In addition, bread crusts without shortening were observed to have lighter colour than those made with shortenings. The hardness, springiness, cohesiveness, gumminess and chewiness of bread samples were found to range between 603.30-1350.7(g), 0.86-0.92(mm), 0.70-0.76, 441.95-1002.90(g), and 353.70-874.3(gmm), respectively. Meanwhile, the texture profile analysis showed that the white bread containing shortening type 100:00 had the least crumb hardness, while those made without shortening had the highest crumb hardness. During storage, DSC showed one endothermic peak for all aging times and the onset temperature ranged from 116.06 to 132.22 ºC; and 123.50 to 139.17 ºC for the 1st day and 7th days, respectively. Meanwhile, the texture analyzer showed that the bread made from shortening formulation 100:00 (PO: PS) had the least crumb firmness, while those made without shortening had the highest crumb firmness. In general, there was no significant difference (p<0.05) between bread samples that were made using 60:40 and control. Thus, this research demonstrated that using RBD palm oil/palm stearin-based shortenings in breadmaking could contribute to a better quality and delay bread staling.